A novel patient decision aid for aftercare in breast cancer patients: A promising tool to reduce costs by individualizing aftercare. (October 2018) - Klaassen, Linda A.; Dirksen, Carmen D.; Boersma, Liesbeth J.; Hoving, Ciska; ,
Abstract: Objective: A patient decision aid (PtDA), was developed to support breast cancer patients making choices about their aftercare. The aim of this pilot was to test the effects of the PtDA on Shared Decision Making (SDM), Decision Evaluation (DES) in patients, consultation time, choice of aftercare and hospital costs. Methods: A prospective before-and-after study including a control (no PtDA-usage) and experimental group (PtDA-usage during consultation) was conducted in six hospitals. Patients were offered a choice between intensive (face-to-face consultations) and less intensive (telephonic or on demand consultations) aftercare. All patients filled out three validated questionnaires (baseline (T0), directly after the consultation (T1), three months later (T2)), assessing demographics (T0), SDM(T1) and DES (T1, T2). Hospital costs and choice of aftercare were assessed from the patients' files (T2). Effect sizes ( ɳp 2 : 0.01 = small; 0.06 = medium; 0.14 = large; φ: 0.1 = small, 0.3 = medium, 0.5 = large) and p-values were calculated using both univariate and multivariate GLMs, a repeated measures GLM and chi-square-tests. Results: A small improvement in SDM ( ɳp 2 = 0.02) and an effect ( ɳp 2 = 0.10) on DES was found in the experimental group. Significantly more PtDA-users (51% vs. 29%, φ = 0.22) chose less intensive aftercare, leading to a small reduction of hospital costs (122 vs. 92 Euro, ɳp 2 = 0.01), and a large increase in average consultation time (12.5 min; ɳp 2 = 0.29). Conclusion: This pilot study showed promising effects of the PtDA on SDM and hospital costs. The PtDA can be developed further to potentially reduce the increased consultation time. Highlights: Effects of a novel aftercare PtDA for breast cancer patients were tested. The PtDA elicits both analytical and intuitive preferences. PtDA-users were significantly more likely to choose less intensive aftercare. Using the PtDA during consultations significantly increased consultation time.